2004
DOI: 10.1002/jsfa.1842
|View full text |Cite
|
Sign up to set email alerts
|

Application of different forms of calcium to tea soil to prevent aluminium and fluorine accumulation

Abstract: Tea Camellia sinensis (L), is a well-known accumulator of aluminium and fluorine from acidic soil. A reduction is desirable as aluminium and fluorine absorbed will leach into the tea liquor through infusion, thus posing a serious threat to the health of consumers. The present study aims to investigate the effects of adding different forms of calcium on Al and F uptake by tea plants, in order to reduce the concentrations of these elements contained in the plants. All true lime materials increased the soil pH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Some foods and beverages, such as certain types of tea, contain high contents of fluoride . Tea is the most popular beverage in the world after water; however, the tea plant is well known to accumulate fluoride . Cases of unsightly dental fluorosis and crippling skeletal fluorosis have been reported, linked to chronic exposure to high levels of fluoride through consumption of (brick) tea .…”
Section: Introductionmentioning
confidence: 99%
“…Some foods and beverages, such as certain types of tea, contain high contents of fluoride . Tea is the most popular beverage in the world after water; however, the tea plant is well known to accumulate fluoride . Cases of unsightly dental fluorosis and crippling skeletal fluorosis have been reported, linked to chronic exposure to high levels of fluoride through consumption of (brick) tea .…”
Section: Introductionmentioning
confidence: 99%
“…The stimulatory effects of Al on C. sinensis were demonstrated by Chenery2 in field studies. Aluminium stimulates the growth of excised roots and also the growth of C. sinensis in solution culture 3–5. In fact, Konishi et al 3 devised a nutrient medium for the solution culture of C. sinensis which includes 1 mmol L −1 Al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Matsumoto et al (1996) reported that tea is one of the few plants that accumulates Al. Al salts present in tea garden soils dissociate at pH < 5.5 and produce Al 3+ in soil solution and form complexes with phosphate (AlPx) at the root surface of tea (Fung and Wong 2004). From our results, both EC and SC tea (compared with black tea from different areas and green tea from different areas) showed no significant differences in Al concentration.…”
Section: Mg Kg _ 1 In Otec Ot Showed the Highest Concentration Ofmentioning
confidence: 58%